Relationships and the challenges / Emily Jothee Mathai - Mathai, Emily Jothee (Academy of Language Studies, 2023)
Have you ever read a book written by Dr. John Gray, an American author and relationship counsellor entitled, “Men are from Mars, Women are from Venus”. It was released in 1992 and became a bestseller. As the title indicates – are men and women species from different planets? Nope! We are all from the planet Earth for sure, but BOTH are distinct from each other emotionally, culturally and in terms of personal values which affect relationships.